Efficiency and productivity of conventional and organic farms in Finland 1994-1997 - Oude Lansink, Alfons; Pietola, Kyösti; Bäckman, Stefan (Oxford University Press, 2002)
This paper uses data envelopment analysis to compute overall technical and inputspecific technical efficiency measures of conventional and organic farms in Finland. Moreover, productivity measures are determined, indicating differences in technology employed by organic and conventional farms. The data are from crop and livestock farms over the period 1994-1997. The results show that organic farms are on average more efficient relative to their own technology, but use a less productive technology than conventional farms.
Keywords: Ma; organic farming; productivity; technical efficiency; Finland; DEA